IMPLEMENTASI POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH DI SMKN 2 DEPOK SLEMAN - Septiana, Ririn Dwi; Sani, Salsa Aulifia; Sekararum, Rizha Devi; Purnamasari, Niken (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The implementation of the Regional Public Service Agency (BLUD) in vocational high schools aims to enhance the flexibility, efficiency, and accountability of school financial management. SMKN 2 Depok Sleman began implementing BLUD in 2024 and faced several adjustments in planning, implementation, reporting, and supervisory processes. This study aims to describe the implementation of BLUD Financial Management at SMKN 2 Depok Sleman. The research employed a qualitative approach with a case study design through interviews and observations, analyzed using the Miles, Huberman, and Saldana model. The results show that financial planning and budgeting are carried out through the bottom-up preparation of the Business Plan and Budget (RBA) at the department level, increasing participation and accuracy in planning. The implementation stage provides flexibility for the school to finance teaching factory activities and operational needs in accordance with regulations. In terms of reporting, the school prepares seven financial statements based on Government Accounting Standards (PSAP) 13 and completes monthly accountability reports as a form of transparency. Additionally, capacity-building programs from DIKPORA and BPKA support the improvement of human resources in managing BLUD. Overall, the implementation of BLUD at SMKN 2 Depok Sleman strengthens the school’s financial independence and improves the quality of financial governance.